The cross-cultural invariance of the servant leadership survey: A comparative study across eight countries - Dirk van Dierendonck; Milton Sousa; Sigrún Gunnarsdóttir; Andrea Bobbio; Jari Hakanen; Armin Pircher Verdorfer; Emin Cihan Duyan; Raquel Rodriguez-Carvajal (Administrative Sciences, 2017)
This paper tests and confirms the cross-cultural equivalence of the Servant Leadership Survey (SLS) in eight countries and languages: The Netherlands, Portugal, Germany, Iceland, Italy, Spain, Turkey and Finland. A composite sample consisting of 5201 respondents from eight countries that all filled out the SLS was used. A three-step approach was adopted to test configural invariance, measurement equivalence, and structural equivalence. For the full 30-item version of the SLS, configural invariance and partial measurement equivalence were confirmed. Implications of these results for the use of the SLS within cross-cultural studies are discussed.
Keywords: 350; servant leadership; cross-cultural; measurement equivalence